2013
DOI: 10.1097/mcg.0b013e3182819a89
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Combination of Simple Noninvasive Fibrosis Scoring Systems Increases Diagnostic Accuracy in Nonalcoholic Fatty Liver Disease

Abstract: The FIB-4 and NAFLD fibrosis scores perform better than the BARD scoring system. Liver biopsy can securely be replaced only with a stepwise combination of simple noninvasive tests, otherwise the assessment of risk due to advanced fibrosis may be misleading in a clinically meaningful proportion of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 34 publications
3
27
0
3
Order By: Relevance
“…Although all the pathologists reading the biopsies are highly experienced hepatopathologists, there is potential for interobserver variability, which may have led to a lowering of the diagnostic accuracy of the tests. Despite these limitations, the overall diagnostic accuracy of the non-invasive scores assessed in the present study are in keeping with other studies and this is the first study to specifically assess these scores in specific age groups (17, 18, 20, 30, 31, 32). …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although all the pathologists reading the biopsies are highly experienced hepatopathologists, there is potential for interobserver variability, which may have led to a lowering of the diagnostic accuracy of the tests. Despite these limitations, the overall diagnostic accuracy of the non-invasive scores assessed in the present study are in keeping with other studies and this is the first study to specifically assess these scores in specific age groups (17, 18, 20, 30, 31, 32). …”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that these scores can reliably exclude advanced fibrosis in patients with NAFLD, and as a result, they provide a useful, inexpensive first-line assessment of liver fibrosis for use in primary or secondary care (16, 18, 19). Although fidelity appears lower when applied in bariatric surgery cohorts (29), several studies have now validated their use in large populations of patients with biopsy-proven NAFLD (17, 20, 30, 31, 32). However, the majority of patients included in these studies were in middle age (typical mean age of 45–55 years), with very few younger (≤35 years) or older patients (≥65 years) included.…”
Section: Discussionmentioning
confidence: 99%
“…Other non‐invasive systems such as AAR and the APRI test were not considered because they were not analyzed in Demir et al. 's study, which was selected in our study. Second, these non‐invasive scoring systems may not indicate changes in liver fibrosis stages because parameters used in these non‐invasive systems were not the crucial biomarkers that reflect the liver fibrosis process.…”
Section: Discussionmentioning
confidence: 99%
“…Its utility seems highest in predicting severe fibrosis, or even cirrhosis, and portal hypertension 51 . Demir et-al 52 found that using the FIB-4 sequentially with the BARD decreased the incidence of misdiagnosis of fibrosis stage. Thus, the role of BARD may be to rule out severe fibrosis, or in conjunction with another noninvasive fibrosis model to predict less severe fibrosis.…”
Section: Introductionmentioning
confidence: 99%